GAMIFICATION IN ENGLISH LANGUAGE TEACHING: ENGAGING STUDENTS THROUGH GAMES - Gavharoy Xomidjonova (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
This article explores the role of gamification in English language teaching (ELT) and its impact on student engagement and learning outcomes. By integrating game mechanics and game-based elements into classroom activities, gamification aims to foster a more interactive, enjoyable, and motivating learning environment. This paper examines the theoretical foundations of gamification, its practical applications, and the results of recent studies on its effectiveness in enhancing language acquisition. The findings suggest that gamification can significantly increase student motivation, participation, and language retention, while fostering a positive classroom atmosphere.